Residential field site training project abstracts - 46th Batch Session: 2003-04, 4th year MBBS students, CMC - Editor, The (Journal of Chittagong Medical College Teachers' Association, 2009)
doi: 10.3329/jcmcta.v19i1.3855 Journal of Chittagong Medical College Teachers' Association 2008: 19(1):56-59